2010
DOI: 10.2522/ptj.20090245
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of the Therapist-Patient Relationship on Treatment Outcome in Physical Rehabilitation: A Systematic Review

Abstract: From this review, the alliance between therapist and patient appears to have a positive effect on treatment outcome in physical rehabilitation settings; however, more research is needed to determine the strength of this association.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

14
345
1
16

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 504 publications
(376 citation statements)
references
References 33 publications
14
345
1
16
Order By: Relevance
“…A recent systematic review concluded that there is an association between therapeutic alliance and treatment outcomes in physical rehabilitation [7]. Therapeutic alliance is reportedly a multi-dimensional concept, including concepts such as rapport, trust, communication, empathy, mutual understanding, compassion and respect [4,5,7,8,10,11], causing difficulty in determining what aspect is responsible for the desired enhanced outcome, or what to measure. We would argue that the concept of 'empathy' is a distinct construct, which is important in the therapeutic alliance [12,13].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent systematic review concluded that there is an association between therapeutic alliance and treatment outcomes in physical rehabilitation [7]. Therapeutic alliance is reportedly a multi-dimensional concept, including concepts such as rapport, trust, communication, empathy, mutual understanding, compassion and respect [4,5,7,8,10,11], causing difficulty in determining what aspect is responsible for the desired enhanced outcome, or what to measure. We would argue that the concept of 'empathy' is a distinct construct, which is important in the therapeutic alliance [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…This is a missed opportunity, since there is now some evidence from empirical work that the relationship between clinicians and patients impacts not only on the satisfaction with healthcare but also on the outcomes of healthcare [3][4][5]. Whilst much of this research has been conducted to explore the relationship between doctors and patients, more recent studies are beginning to focus on the relationship between rehabilitation therapists and their patients [6][7][8][9]. A recent systematic review concluded that there is an association between therapeutic alliance and treatment outcomes in physical rehabilitation [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, they were not specifically instructed or trained in behavior change techniques. Increasing evidence shows that the nature of the therapeutic relationship between the physiotherapist and the patient influences treatment adherence and clinical outcomes (24). Adherence is greater when practitioners are perceived as supportive rather than paternalistic (25).…”
mentioning
confidence: 99%
“…Thus, a therapist-patient relationship of trust and safety is established, motivating the patient during treatment to achieve improvement in their pain (9) . One study demonstrated that commitment between patient and therapist correlates positively with treatment outcomes in physical rehabilitation programs, including: ability to perform daily life activities, pain, specific physical functional tasks, depression, global assessment of physical health, adherence to treatment and satisfaction with treatment (10) . In the pedagogical clinics connected to higher education institutions, where the attendance is carried out by students who are in the last year of undergraduate training under the supervision of Physiotherapy professors with, at least, a specialist title depending of the institution.…”
Section: Introductionmentioning
confidence: 99%